Implementation of a practical and effective pilot intervention against transmission of Taenia solium by pigs in the Banke district of Nepal. - Ishab Poudel; Keshav Sah; Suyog Subedi; Dinesh Kumar Singh; Peetambar Kushwaha; Angela Colston; Charles G Gauci; Meritxell Donadeu; Marshall W Lightowlers (PLoS Neglected Tropical Diseases, 2019)
Taenia solium is a zoonotic cestode parasite which causes human neurocysticercosis. Pigs transmit the parasite by acting as the intermediate host. An intervention was implemented to control transmission of T. solium by pigs in Dalit communities of Banke District, Nepal. Every 3 months, pigs were vaccinated with the TSOL18 recombinant vaccine (Cysvax, IIL, India)) and, at the same time, given an oral treatment with 30mg/kg oxfendazole (Paranthic 10% MCI, Morocco). The prevalence of porcine cysticercosis was determined in both an intervention area as well as a similar no intervention control area, among randomly selected, slaughter-age pigs. Post mortem assessments were undertaken both at the start and at the end of the intervention. Participants conducting the post mortem assessments were blinded as to the source of the animals being assessed. At the start of the intervention the prevalence of porcine cysticercosis was 23.6% and 34.5% in the control and intervention areas, respectively. Following the intervention, the prevalence of cysticercosis in pigs from the control area was 16.7% (no significant change), whereas no infection was detected after complete slicing of all muscle tissue and brain in animals from the intervention area (P = 0.004). These findings are discussed in relation to the feasibility and sustainability of T. solium control. The 3-monthly vaccination and drug treatment intervention in pigs used here is suggested as an effective and practical method for reducing T. solium transmission by pigs. The results suggest that applying the intervention over a period of years may ultimately reduce the number of tapeworm carriers and thereby the incidence of NCC.